CUSTOMER SATISFACTION AND PURCHASE INTENTION EFFECTS ON LAPTOP SALES PERFORMANCE - Aditya Putra Kusuma (PT. Media Akademik Publisher, 2026)
This study examines the effects of customer satisfaction and purchase intention on laptop sales performance at Digital Computer Store. In an increasingly competitive retail technology market, understanding consumer-related factors is essential for sustaining sales growth. This research aims to analyze both the partial and simultaneous influence of customer satisfaction and purchase intention on sales outcomes. A quantitative approach was employed using survey data collected from 57 consumers, which were analyzed through multiple linear regression. The findings indicate that customer satisfaction has a positive and significant effect on laptop sales, highlighting the importance of service quality, product suitability, and post-purchase experience in encouraging repeat purchases. Purchase intention also demonstrates a positive and significant influence, reflecting consumers’ readiness to buy shaped by promotions, perceived value, and trust. Simultaneously, both variables explain a substantial proportion of the variation in sales performance, confirming their strategic relevance in retail management. These results imply that sales performance in technology retail is driven not only by product availability but also by consumers’ perceptions and behavioral intentions. Therefore, integrating customer satisfaction initiatives with strategies that stimulate purchase intention is crucial for achieving sustainable sales performance and strengthening competitive advantage.